Features of the use of public-private partnerships in the production of solar energy - Abayev, A.; Yessengeldin, B.; Mukhamediyeva, G.; Kalykov, A. (BUKETOV BUSINESS REVIEW, 2024)
Object: The purpose of the article is to study the effectiveness of introducing public-private partnership mechanisms in the production of solar energy. In the article areas that will contribute to the development of solar energy production were discussed. Methods: The article uses theoretical, analytical and comparative methods to determine the possibility of using public-private partnership mechanisms in the production of solar energy. These methods are based on results obtained from data from the International Renewable Energy Agency, scientific concepts obtained in scientific articles by scientists. Findings: The article examines the main problems of using public-private partnerships in the production of solar energy, discussed in the scientific works of scientists: tensions associated with land disputes; insufficiency of special legislation; risk reduction mechanisms; division of information flows between different sectors; distribution of profits and losses between interested parties; implementation of technologies; attracting foreign investment. The analysis identified mechanisms for attracting the necessary investments and reducing possible risks in the production of solar energy on the basis of public-private partnerships. Conclusions: The article provides recommendations for the production of solar energy, taking into account publicprivate partnerships: providing information on planned and ongoing projects; use of state guarantees to reduce risks in the allocation of land plots; the use of clear mechanisms for the distribution of initial costs between the state, the private sector and the population.